Experimental investigation of combustion hot-gas ventilated supercavitation - Van-Duyen Pham; Ji-Woo Hong; Byoung-Kwon Ahn (International Journal of Naval Architecture and Ocean Engineering, 2022)
Most of experimental and numerical studies on ventilated supercavitation have been focused on injection of room temperature air. However, in this work, the effect of combustion hot-gas over 1200 K on characteristics of the supercavity was investigated. Experiment was conducted at a cavitation tunnel using a methane-oxygen combustor designed and manufactured in-house. The results reveal that the high-temperature gas has the effect on reducing fluctuation of the supercavity compared with room temperature gas; variation of the supercavity length is reduced by up to 60% at a certain condition. In this experiment, the development process of the supercavity was strictly observed using two high-speed cameras from the side and top of the test section. Throughout analysis of high-speed shadow images, a reverse flow inside the supercavity was observed and this physical mechanism was conceptually explained. Furthermore, the results show that the temperature variation inside the supercavity depends on the ventilation gas rate, whereas the pressure remains constant after reaching the minimum cavitation number and creating a transparent supercavity. In addition, it was observed that the water-gas interface of the supercavity becomes unstable as the temperature of the injection gas increases and wiggles on the cavity surface become more severe.